An Evidence-Based Approach to Defining Fetal Macrosomia - Froehlich, Rosemary; Simhan, Hyagriv N.; Larkin, Jacob C. (American Journal of Perinatology, 2016)
Objective This study aims to determine the risk of adverse outcomes associated with the current diagnostic criteria for fetal macrosomia.Study Design We evaluated three techniques for characterizing birth weight as a predictor of shoulder dystocia or third- or fourth-degree laceration in 79,879 vaginal deliveries. First, we compared deliveries with birth weights above or below 4,500 g. We then performed logistic regression using birth weight as a continuous predictor, both with and without fractional polynomial transformation. Finally, we calculated the number of cesarean sections required to prevent one incident of the interrogated outcomes (number needed to treat [NNT]).Results Rates of adverse intrapartum outcomes increase incrementally with increasing birth weight and are predicted most accurately with logistic regression following fractional polynomial transformation. The NNT for third- or fourth-degree laceration dropped from 14.3 (95% confidence interval [CI], 13.9–14.7) at a birth weight of 3,500 g to 6.4 (95% CI, 6.1–6.8) at 4,500 g and, for shoulder dystocia, from 54.9 (95% CI, 51.5–58.6) at 3,500 g to 5.6 (95% CI, 5.2–6.0) at 4,500 g.Conclusion The conventional distinction between “normal” and “macrosomic” does not reflect the incremental effect of increasing birth weight on the risk of obstetric morbidity. Outcomes analysis can inform fetal growth standards to better reflect relevant thresholds of risk.
Keywords: macrosomia; fetal growth standards; shoulder dystocia